Cortisol Reactivity and Observed Parenting among Mothers of Children with and without ADHD. Issue 12 (October 2022) - Thomas, Sharon R.; Woods, Kelsey E.; Mazursky-Horowitz, Heather; Novick, Danielle R.; Dougherty, Lea R.; Glasper, Erica R.; Chronis-Tuscano, Andrea
Objective: Neurobiological models suggest links between maternal cortisol reactivity and parenting; however, no studies have examined cortisol reactivity and parenting in mothers of school-age children with ADHD. Method: We examined the relationship between observed parenting and maternal cortisol reactivity in two laboratory contexts: the Trier Social Stress Task (TSST) and parenting-child interaction (PCI). Mothers of children with ( N = 24) and without ( N = 36) ADHD participated. Results: During the TSST, greater cortisol output and increase were associated with decreased positive and increased negative parenting. However, during the PCI, cortisol output was associated with increased self-reported and observed positive parenting, and decreased observed negative parenting. Cortisol change during the PCI was associated with decreased observed positive parenting and increased self-reported negative parenting. Among mothers of children with ADHD, cortisol output during the PCI was negatively associated with negative, inconsistent parenting. Change in cortisol predicted more inconsistent discipline and corporal punishment. Conclusion: Findings contribute to an integrative biological, psychological, and cognitive process model of parenting in families of children with ADHD.